Thermodynamic modeling of the aluminum–iron–oxygen system. (December 2015) - Lindwall, Greta; Liu, Xuan L.; Ross, Austin; Fang, Huazhi; Zhou, Bi-Cheng; Liu, Zi-Kui
Abstract: The aluminum–iron–oxygen (Al–Fe–O) system is an important subsystem within several material classes, especially when considering oxidation of high-performance structural materials or deoxidation of steels during steelmaking. Despite its industrial importance as well as the large amount of experimental information available in literature, no complete phase diagram has been reported for this system. Therefore, a thermodynamic description, by means of the CALPHAD method, is developed in this study. To account for the complexity of the solid oxides including non-stoichiometry, solid solution in the phases and cation distribution between different lattice sites, the compound energy formalism is applied for the modeling. The liquid phase is modeled utilizing the ionic two-sublattice model. The sublattice models are selected with the aim to achieve compatibility with the Al–Ni–O and Fe–Ni–O systems to facility development of a quaternary thermodynamic description. The evaluated model is validated by comparison to available experimental data. Satisfactory agreement with both thermochemical and phase equilibrium data is concluded. Highlights: A thermodynamic model of the Al–Fe–O system is presented. The oxides' solid solutions and the cation distribution between different lattice sites in the oxides are accounted for. Compatibility with Fe–Ni–O and Al–Ni–O is enabled for the aim to develop a Al–Fe–Ni–O model.